Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

10 + 2(7 - 9x) = 5(2x - 12)


Full steps as well please


Sagot :

Answer:

x = 3

Step-by-step explanation:

10 + 2(7 - 9x) = 5(2x - 12)

10 + 14 - 18x = 10x - 60

24 - 18x = 10x - 60

+60                 +60

-------------------------------------

84 - 18x = 10x

     +18x    +18x

-------------------------------------

84 = 28x

/28    /28

--------------------------------------

3 = x

Answer:

x = 3

Step-by-step explanation:

Do multiplication for the parenthesis terms, then add and subtract accordingly.

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.